Uganda Strategy Support Program (USSP) - International Food Policy Research Institute (2010)
The Uganda Strategy Support Program (USSP) website is a medium for circulating information relevant to Uganda's agriculture policy and strategy development. The blog contains updates on USSP's work - ongoing research, upcoming events, publications, findings - as well as general information to support agricultural researchers and policymakers.